SOBRE ÁRBITROS, TRADUCTORES Y CELESTINAS. LA FIGURA DEL MEDIADOR COMO INSTANCIA METACOMUNICATIVA - Lucerga Pérez, María José (Revista de Investigación Lingüística, 1997)
The models used till now in the semiotic studies start from the premise that communication is a bipolar phenomenon, played mainly by senders and receivers -or interlocutors-. However, a lot of interactive situations are only possible due to the intervention of a different figure, a third one we have designated as "Mediator". Using this term in a wider perspective than the one employed when its refers to mediation as a professional field, the present article examines this third figure, proposing its inclusion within the semiocommunicative frame and describing it as a metacommunication application responsible for defining the meeting, coordinating its development and establishing the relationship between the participants. Criteria of categorization and a first approachment to a typology of the mediation processes are also offered in this article.